"In my life, I have always gone either crookedly or against the current!": Andreas Karayan's Pioneering, Queer Counter-narrative in 20th c. Cypriot Art - Danos, Antonis (My University, 2022)
The pioneering depiction of male nudes by the Cypriot painter (and more recently, writer of semi-biographical literary works) Andreas Karayan (b. 1943), caused quite a stir in the Cypriot art scene when exhibited from the late 1970s onwards. Using Constantine Cavafy’s poetry as a starting point and recurring reference, Karayan portrayed the male nudes as both sexual(ized) subjectivities, as well as – because of their eroticism – embodiments of social protest and queer subversion. Even more subversive, however, were some other works, from the late 70s and through the 80s. These were images of (fully dressed) young men in public spaces – bus stops, streets, coffee shops – and of sailors and soldiers in seemingly banal conditions (for instance, resting before or after an official parade). Such works not only brought, literally, into the open, (homo)erotic desire (gazes are exchanged, seeking a response, or are directed toward the viewer), but they are also imbued with political irony and critique, which foregrounded and interrogated issues of power, desire, and national and other “sacred” symbols of collective identity. The (seemingly anachronistic) classicist/realist style of his works made them more accessible to the local art-scene public, who made the comfortable yet superficial connection with the already established, aestheticized images of soldiers and sailors by Greek painter Yiannis Tsarouchis (1910-89). This enabled the queer counter-narrative of Karayan’s works to reach a wider audience.
Keywords: Queer art; Cyprus; 20th century